Traditional Values of the Hajat Sasih Ceremony in Kampung Naga as a Social Studies Learning Sources - Hoerul Anam, Rifki; Rizkiani Sundara, Ilmi; Dahlena, Alni; Tetep (Institut Pendidikan Indonesia, 2023)
The purpose of this study is to expand social studies learning resources based on local wisdom in the community by introducing the traditional values of the hajat sasih ceremony in Kampung Naga as a source of social studies learning for students. The research method of this thesis uses a qualitative approach with descriptive research methods with observation, documentation and interviews with traditional leaders of the Kampung Naga community, local government and educators and students in schools. The results of this study are 1). The values contained in the implementation of the hajat sasih ceremony tradition include religious values, social values and cultural values, 2). The educators at SMPN 2 Salawu strongly support and implement the use of learning resources based on local wisdom by using the tradition of the Hajat Sasih ceremony in Kampung Naga as a social studies learning resource based on the adaptation results of basic learning competencies, 3). The results of internalization at SMPN 2 Salawu students gave very good responses to local wisdom-based learning related to their environment, students showed positive reactions and liked it very much. The values of the local wisdom of the Hajat Sasih tradition can be used as a social studies learning resource by identifying the values of the local wisdom of the hajat sasih ceremony and then adjusting them to the basic competencies of learning.